Historically Transvaluating Newspaper of the Colonial Rule - Dr. Rafia Tahir, Anum Mahmood (Journal of Research in Humanities, 2023)
The research paper centers on the timeline of the newspapers from the pre-partition period to the creation of Pakistan. The paper focuses on the journey of newspapers of the sub-continent, ordinarily patronized by the Muslim leadership of the time. The research also focuses on the efforts and contributions led by eminent leadership during the foundational years. The culture of making a caricature was newly adopted during the rule of the British in the sub-continent. These earliest newspapers caricatured colonial India, produced human experience, and shaped colonial affect bringing renowned cartoonists, writer and poets associated themselves with the success of one of the earliest newspaper. From Punch to the Halal e Pakistan all have been deliberated in detail through this research.